The isolation and characterization of mutants of the integration host factor (IHF) of Escherichia coli with altered, expanded DNA-binding specificities. - Lee, E C (1992)
The integration host factor (IHF) of Escherichia coli is a small, basic protein that is required for lambda site-specific recombination and a variety of cellular processes. It is composed of two subunits, alpha and beta, that are encoded by the himA and hip (himD) genes, respectively. IHF is a sequence-specific DNA-binding protein and bends the DNA when it binds. We have used the bacteriophage P22-based challenge phage selection to isolate suppressor mutants with altered, expanded DNA binding specificities. The suppressors were isolated by selecting mutants that recognize variants of the phage lambda H'IHF recognition site. Two of the mutants recognize both the wild-type and a single variant site and contain amino acid substitutions at positions 64 (Pro to Leu) or 65 (Lys to Ser) of the alpha subunit. These substitutions are in a region of the protein that is predicted to contain a flexible arm that interacts with DNA. Three other mutants, which recognize the wild-type and a different variant site, contain amino acid substitutions at position 44 (Glu to Lys, Val or Gly) of the beta subunit. These substitutions are in the middle of a predicted beta-strand of the subunit. We discuss the possible mechanisms of suppression by the mutants in terms of a model of the IHF-DNA complex proposed by Yang and Nash [Cell, 57, 869-880 (1989)].